Bounce Forward Better: Geriatric and Gerontological Research in the Post-pandemic Future - Jee-Hyun Noh; Hidenori Arai; Tung Wai Auyeung; Matteo Cesari; Walter R. Frontera; Hyuk Ga; Hee-Won Jung; Wee Shiong Lim; Jae-Young Lim (Annals of Geriatric Medicine and Research, 2022)
In recent years, we have faced challenges in managing coronavirus disease 2019 (COVID-19), especially in older adults. The pandemic has precipitated a global health crisis that impeded older adults from maintaining their health. Disruption of the routine management of chronic diseases, physical inactivity deteriorating physical function and quality of life, malnutrition, and mental disorders have been suggested as major threats to the health of older adults. To address these problems and facilitate reactivation of normal care activities, this article summarizes the contents of a webinar held by the Annals of Geriatric Medicine and Research (AGMR) regarding the future directions of geriatric medicine and research in the post-COVID-19 era.